Aesthetics in architecture: unity of form, function and meaning - Cheng, Fangyu (2024)
In modern architectural design, “formal beauty” and “functional beauty” have become a new concept. At present, architects have gradually attached importance to the functional and aesthetic aspects of architecture in contemporary architectural design, and have pursued a comprehensive approach. This article provided corresponding countermeasures on how to enhance the functional and formal beauty in architectural design. By discussing and emphasizing the key role of architectural aesthetics in modern architectural design, the balance between aesthetics and practicality can be promoted to meet the contemporary society’s needs. By exploring the connotation of architectural aesthetics, this article briefly summarized and explored the meanings of functional beauty and formal beauty in architectural design, emphasizing the application of architectural formal beauty in modern architectural design. In real life, architectural aesthetics, through the comprehensive embodiment of formal beauty, functional beauty and symbolic beauty, not only provides people with actual living space, but also enriches people’s life experience through its appearance, connotation and symbolic significance, shapes the city’s and society’s face, and becomes a part of culture and history. In different historical periods, architectural aesthetics have the times’ different characteristics. In modern society, there have been more new developments and changes in architectural aesthetics. Among them, the unity of function and form is one of the most important features in architectural aesthetics. At the same time, with the changes of social history and cultural concepts, architectural aesthetics also reflects the times’ certain characteristics. This article explored the integration of functional beauty, formal beauty, and meaningful beauty in modern architecture from the perspective of modern architecture, and promoted the development of modern architectural art through scientific methods. This paper emphasized the importance of pursuing the unity of form and function in architectural design. This means that the building should not only be attractive in appearance, but also meet the actual needs and functional requirements. This unity can create beautiful and practical architectural works.